A return to harmful alcohol consumption impacts on portal hemodynamic changes following alcoholic hepatitis. Issue 8 (August 2018) - Spahr, Laurent; Goossens, Nicolas; Furrer, Flavie; Dupuis, Melissa; Vijgen, Sandrine; Elkrief, Laure; Giostra, Emiliano; Rubbia-Brandt, Laura; Frossard, Jean-Louis
Abstract : Background: Increased hepatic venous pressure gradient (HVPG) plays a role in the clinical manifestations of alcoholic hepatitis (AH). The evolution of HVPG and the influence of alcohol use in the intermediate term are unclear. Aim: The aim of this study was to explore HVPG modifications following AH taking into consideration alcohol use and clinical manifestations. Patients and methods: Patients with AH ( n =37; age 52 years; model for end-stage liver disease: 18.5; Maddrey score: 43) and chronic excessive drinkers with compensated cirrhosis ( n =19; age: 54 years; model for end-stage liver disease: 9.2) underwent HVPG measurement and liver biopsy. Ten long-standing abstinent alcoholic cirrhotics served as controls. After discharge, patients were monitored for alcohol use and clinical complications, with repeated HVPG after a median duration of 100 days. Inflammation was determined using plasma C-reactive protein. Results: At baseline, compared with chronic excessive drinkers and alcoholic cirrhotics, patients with AH had increased HVPG (18.1±0.6 vs. 13.8±1.4 vs. 15±1.3 mmHg, P <0.05). During follow-up, patients who became abstinent or reported occasional drinking were more likely to achieve a greater than 20% reduction in HVPG compared with those returning to harmful alcohol (45 vs. 0%, P <0.01), and suffered from fewer complications (25 vs. 68%, P <0.03). High baseline C-reactive protein levels correlated to the Maddrey ( r =0.38), but no relationship was observed between changes in inflammation and HVPG. Conclusion: Elevated HVPG is a feature of AH, with a clinically significant reduction in values in abstinent or occasional drinkers after weeks of follow-up. A return to harmful alcohol has a negative impact on portal hemodynamics and associated clinical complications.